The know-how of face transplantation - Siemionow, Maria Z. (Springer, 2011)
The book is laid out in 6 sections: 1. Preclinical Approaches to Face Transplantation 2. Clinical Aspects in Preparation to Face Transplantation in Humans 3. Approval Process of Face Transplantation in Humans 4. Social and Public Relations in Face Transplantation 5. World Experience with Face Transplantation in Humans 6. Future Directions in Face Transplantation This book spans the entire process of a face transplantation, from detailing the anatomy of the face to considering the social and ethical challenges of the procedure. This rigorous presentation of face transplantation also includes the anesthesia involved, the role of Institutional Review Boards in approving the operation, the financial aspects and media response. Since the authorship is international, the book considers the different perspectives, approaches and responses from across the world.